Hidup Bersama Saudara Autistik Saya: Studi Fenomenologi - Armand, Ghianina Yasira; Handayani, Eko; Mansoer, Winarini Wilman (INSAN Jurnal Psikologi dan Kesehatan Mental, 2024)
This research aims to understand the experiences and meaning of individuals who have siblings with autism spectrum disorder (ASD). Participants were seven individuals aged 12 to 25 years who had siblings with ASD living in Indonesia. Data were collected through 60-90 minute semi-structured interviews discussing their personal experiences and perspectives on daily life with their autistic sibling. The interview results were analyzed using thematic analysis which found four main themes: early experiences post siblings' diagnosis, implication on siblings, siblings' relationships, and siblings' perspectives. Young adult participants shared the process of receiving siblings' diagnosis that were influenced by age, how it was communicated by parents, and their own viewpoint of the diagnosis, several adjustments they had to withstand up to their acceptance of the siblings' condition. They also described caregiving role and responsibility for their siblings' future, whereas adolescent participants expressed their own struggles, hope and needs for siblings' recovery.